2013
DOI: 10.1089/met.2013.0010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in People Suffering from Posttraumatic Stress Disorder: A Systematic Review and Meta-Analysis

Abstract: Despite some limitations, the findings of this systematic review and meta-analysis confirmed our hypothesis that individuals suffering from PTSD have a greater risk of metabolic syndrome. The potential role of unknown factors or mediators that might clarify the nature of this association needs further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 51 publications
7
60
0
1
Order By: Relevance
“…Similarly, 19%-26% of the patients with schizophrenia met at least two criteria and 23%-26% of the patients fulfilled at least one criterion of metabolic syndrome. The prevalence of metabolic syndrome in these patients is close to the 36% of 1 PTSD patients with metabolic syndrome reported by Bartoli et al 6 Thus, it remains unclear whether PTSD confers any special risk for metabolic syndrome when compared with other psychiatric disorders.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Similarly, 19%-26% of the patients with schizophrenia met at least two criteria and 23%-26% of the patients fulfilled at least one criterion of metabolic syndrome. The prevalence of metabolic syndrome in these patients is close to the 36% of 1 PTSD patients with metabolic syndrome reported by Bartoli et al 6 Thus, it remains unclear whether PTSD confers any special risk for metabolic syndrome when compared with other psychiatric disorders.…”
supporting
confidence: 54%
“…1 The importance of metabolic syndrome is that it confers at least a two-fold increased risk of cardiovascular disease and at least five-fold increased risk for subsequent diabetes. [2][3][4][5] In their report in Metabolic Syndrome and Related Disorders, Bartoli et al 6 study the association of posttraumatic stress disorder (PTSD) and metabolic syndrome. The authors found six studies that met their criteria for inclusion in their meta-analysis involving 528 subjects with PTSD and 846 comparison patients; 5 of these had at least a trend toward a positive association.…”
mentioning
confidence: 99%
“…Key words used were "metabolic syndrome" AND "posttraumatic stress disorder" in the title, abstract or index term fields. Manual searches were also conducted using the reference lists from recovered articles and the meta-analysis of Bartoli et al [19]. After the removal of duplicates, both reviewers screened the titles and abstracts of all potentially eligible articles.…”
Section: Search Criteria Study Selection and Critical Appraisalmentioning
confidence: 99%
“…Early life and chronic stress may have a negative impact on feeding behaviours leading to poor dietary habits and low exercise activity via altering hypothalamic-pituitary-adrenal (HPA) axis response and orexigenic or anorexigenic hypothalamic neuropeptides [3][4][5]. Indeed, it has been shown that individuals with the history of childhood trauma and those with a diagnosis of post-traumatic stress disorder (PTSD) are characterized by increased cardio-metabolic risk [6][7][8]. Although the relationship between stress and metabolic dysregulation has been widely investigated in the general population and PTSD cases, these issues have been addressed only in one study on first-episode psychosis patients [9].…”
Section: Introductionmentioning
confidence: 99%